Polyamine signal through gap junctions: A key regulator of proliferation and gap‐junction organization in mammalian tissues?. (29th April 2016) - Hamon, Loic; Savarin, Philippe; Pastré, David
Abstract : We propose that interaction rules derived from polyamine exchange in connected cells may explain the spatio‐temporal organization of gap junctions observed during tissue regeneration and tumorigenesis. We also hypothesize that polyamine exchange can be considered as signal that allows cells to sense the proliferation status of their neighbors. Polyamines (putrescine, spermidine, and spermine) are indeed small aliphatic polycations that serve as fuels to sustain elevated proliferation rates of the order observed in cancer cells. Based on recent reports, we consider here that polyamines can be exchanged through gap junction channels between mammalian cells. Such intercellular exchange of polyamines has critical consequences on the local control of growth. In line with this hypothesis, the complex protein network that keeps polyamine levels finely tuned in mammalian cells can translate polyamine efflux or influx into integrated signals controlling transcription, translation, and cell communications. Abstract : While only polyamine synthesis or transport and their respective roles in cancer were considered so far, we propose that polyamine exchange through gap junctions also matters, and constitutes a signal that regulates both proliferation and the organization of gap junctions in mammalian tissues.